I want to tell you: my response to your letters, your messages, your questions - Simpson, Orenthal J. (Memoir, 1995)
As O.J. waits to be judged by a jury of his peers, his commentary, thoughts, and relections are juxaposed with letters selected from the more than 300,000 he has received from people across the United States, since being incarcerate at the Los Angeles County Jail. The author shares his thoughts on his life with Nicole Brown Simpson, his children, the media, the judicial system, spouse abuse, religion, racism, and his innocence of the murder of his wife.